Sustainable Nanotechnology in Stir-Cast Al Composites: Mechanical Performance in Energy Applications - Sathish S.; Prasad A.V.S Ram; Reddy G. Bharath; Kumar S. Naveen; Ram S.; Gehlot Anita; Singh Navjot (E3S Web of Conferences)
The integration of sustainable nanotechnology into aluminum composites offers significant potential for enhancing mechanical and tribological properties, particularly in energy-related applications. Aluminium alloys are extensively utilised in the aerospace and automotive industries. Due to its low density, superior mechanical characteristics, improved resistance to corrosion and wear, and lower thermal coefficient of expansion as compared to other metals and alloys, From a scientific and technological point of view, these materials are highly interesting applicants for a range of applications due to their good mechanical qualities and relatively low cost of manufacturing. Combining the advantageous qualities of metals and ceramics is the goal of producing metal matrix composite materials. The current research focuses on examining the behaviour of an aluminum cast alloy with a composite made of molybdenum disulphate using the stir casting method. Specimen obtained by the stir casting method were subjected to wear tests and hardness tests. The resultant composites demonstrated improved hardness and wear behavior, making them highly suitable for applications in energy sectors. This research emphasizes the role of sustainable nanotechnology in advancing aluminum-based materials for energy applications, contributing to both performance efficiency and environmental sustainability.